Pengaruh Kerjasama Tim Dan Disiplin Kerja Terhadap Kinerja Karyawan Di Hotel Golden Palace Lombok - Anggita Diadara; M. Ahyat; Putri Reno Kemala sari (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This research aims to determine the effect of teamwork and work discipline on employee performance at the Golden Palace Lombok Hotel partially and simultaneously. The independent variables in this research are Teamwork (X1) and Work Discipline (X2), while the independent variable is employee performance (Y). The population of this study were employees of the Golden Palace Hotel with sample determination using purposive sampling with the criteria of employees having a service period of > 2 years so that a sample size of 32 respondents was obtained. The data obtained was processed using the SPSS version 26 statistical application. The research results showed that teamwork and work discipline had an influence on employee performance at the Golden Palace Lombok Hotel, both partially and simultaneously.